2022
DOI: 10.3390/vaccines10050771
|View full text |Cite
|
Sign up to set email alerts
|

Disclosing Potential Key Genes, Therapeutic Targets and Agents for Non-Small Cell Lung Cancer: Evidence from Integrative Bioinformatics Analysis

Abstract: Non-small-cell lung cancer (NSCLC) is considered as one of the malignant cancers that causes premature death. The present study aimed to identify a few potential novel genes highlighting their functions, pathways, and regulators for diagnosis, prognosis, and therapies of NSCLC by using the integrated bioinformatics approaches. At first, we picked out 1943 DEGs between NSCLC and control samples by using the statistical LIMMA approach. Then we selected 11 DEGs (CDK1, EGFR, FYN, UBC, MYC, CCNB1, FOS, RHOB, CDC6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 88 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated that YY1 can act as a transcriptional activator and repressor, depending on its associated partners and sequences surrounding its binding sites [20,21]. Studies have also observed YY1 expression to be associated with tumor recurrence and tumorigenesis [22][23][24]. However, a study demonstrated that YY1 might have tumor-suppressing properties through the inhibition of c-Myc transforming activity [25].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that YY1 can act as a transcriptional activator and repressor, depending on its associated partners and sequences surrounding its binding sites [20,21]. Studies have also observed YY1 expression to be associated with tumor recurrence and tumorigenesis [22][23][24]. However, a study demonstrated that YY1 might have tumor-suppressing properties through the inhibition of c-Myc transforming activity [25].…”
Section: Discussionmentioning
confidence: 99%
“…High miR-335-5p expression promotes bone formation and regeneration ( Zhang et al, 2017 ) and angiogenesis ( Walz et al, 2019 ) and regulates cancer progression by targeting MAPK10 ( Gao et al, 2021 ) or NLRP1/7 ( Lin W. et al, 2021 ). Furthermore, a FOXC1 and miR-335-5p network was presented in non-small-cell lung cancer ( Mosharaf et al, 2022 ), type 2 diabetes ( Rahman et al, 2020 ), and vascular dementia ( Shu et al, 2022 ). The dermis of keloid and SSc is known to be made up of newly formed vessels ( Trojanowska, 2010 ; Ogawa, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we recommended our proposed BC-causing five upregulated (COL11A1, COL10A1, CD24, PLK1, UBE2C) and three down-regulated (PDK4, CD36, ACACB) HubGsguided top-ranked six ligands/molecules (Suramin, Rifaximin, Telmisartan, Tukysa Tucatinib, Lynparza Olaparib, TG.02) as the candidate drug molecules by molecular docking analysis. It should be mentioned here that both upregulated and down-regulated HubGs were used as drug targets in different studies [166][167][168][169]. Upregulated HubGs-guided drugs inhibit the upregulation of HubGs, while down-regulated HubGs-guided drugs activate the downregulation of HubGs [170].…”
Section: Discussionmentioning
confidence: 99%